Extracellular Matrix Targeted MRI Probes. Issue 1 (8th September 2022) - Digilio, Giuseppe; Lacerda, Sara; Lavin Plaza, Begoña; Phinikaridou, Alkystis
Abstract: Dysregulated remodeling of the extracellular matrix (ECM) can lead to excessive accumulation of ECM proteins (primarily collagen, elastin/ tropoelastin, fibronectin and fibrin) resulting in tissue fibrosis. In many pathologies, changes in the molecular pattern of ECM components have been related to the progression and severity of fibrosis. Thus, magnetic resonance imaging (MRI) probes sensing specific ECM components hold promise for accurate staging of fibrotic diseases. This paper focuses on gadolinium‐based contrast agents (GBCA) targeted to ECM components, including structural proteins and enzymes. According to available examples, they can be grouped into: 1) GBCA conjugated to targeting vectors that recognize and non‐covalently bind to specific sites on the molecular target; 2) GBCA carrying a reactive chemical function able to bind covalently to the complementary chemical function of the molecular target; and 3) enzyme‐responsive probes, whose relaxivity and pharmacokinetics change after enzymatic processing. Pros and cons of each approach are discussed. Abstract : Gadolinium based MRI probes targeted to ECM components, either proteins or enzymes, hold promise for accurate molecular characterization and staging of fibrotic diseases in vivo. Non‐covalent binding probes (1), reactive probes (2), and enzyme‐responsive probes (3) are discussed.